Countering the Cognitive, Linguistic, and Psychological Underpinnings Behind Susceptibility to Fake News: A Review of Current Literature With Special Focus on the Role of Age and Digital Literacy - Gaillard, Stefan; Oláh, Zoril A.; Venmans, Stephan; Burke, Michael (Frontiers in Communication, 2021)
Fake news, designed to create confusion and lower trust, is now viewed as one of the greatest threats to democracy. It is becoming increasingly evident that to tackle the problem of fake news, an interdisciplinary collaboration is needed. This article evaluates the main findings of recent literature from an integrated psychological, linguistic, cognitive, metacognitive, and sociological perspective, with a particular regard on the interplay of digital and age-related aspects of fake new. Providing a socio-psychological sketch of the fake news believer, the literature describes one as well-intentioned and critical, yet having overconfidence in their own intuition and their ability to ascertain the truth. Linguistically, fake news can be understood as a form of persuasion. While computational (big data) initiatives are employed to halt the spread with some success, hurdles remain. Although the differences in reading comprehension between digital versus paper reading seem inconclusive for now, recently probed metacognitive strategies (by having participants freely allocate reading time) established relevant differences on how information is processed. Additionally, cognitive retreat, shallow processing and overconfidence are also associated with digital reading which might make readers less likely to engage in the cognitive effort fake news detection requires. However, the compounding aspects of aging for the quickly digitizing older generations (decreased processing speed, metacognition, and ability to multitask) are regrettably not accounted for in most current research on factors influencing susceptibility to fake news. Our meta-analysis showed that 74% of behavioral studies looking at fake news largely ignore age (N=62). This age discrepancy is crucial, as many provisional programs set up in the past few years aim at training ways to detect fake news are aimed at younger – digitally native – age groups. As a result, these efforts might not be efficacious and could be improved upon. In this paper we argue that age must become a larger focus in fake news research and efforts in educating people against fake news must expand outside of isolated areas and include older generations.